Unmet needs for HIV ancillary care services by healthcare coverage and Ryan White HIV/AIDS program assistance. (1st August 2022) - Dasgupta, Sharoda; Crim, Stacy M.; Dawson, Lindsey; Kates, Jennifer; Weiser, John; Klein, Pamela W.; Dempsey, Antigone; Hauck, Heather; Lu, Jen-Feng; Shu, Fengjue; Beer, Linda
Abstract : Objective: To investigate unmet needs for HIV ancillary care services by healthcare coverage type and Ryan White HIV/AIDS Program (RWHAP) assistance among adults with HIV. Design: We analyzed data using the 2017–2019 cycles of the CDC Medical Monitoring Project, an annual, cross-sectional study designed to produce nationally representative estimates of characteristics among adults with diagnosed HIV. Methods: Unmet need was defined as needing, but not receiving, one or more HIV ancillary care services. We estimated prevalence ratios (PRs) and 95% confidence intervals (CIs) using predicted marginal means to examine associations between healthcare coverage type and unmet needs for HIV ancillary care services, adjusting for age. Associations were stratified by receipt of RWHAP assistance. Results: Unmet needs for HIV ancillary care services were highest among uninsured persons (58.7%) and lowest among those with private insurance living with at least 400% of the federal poverty level (FPL; 21.7%). Uninsured persons who received RWHAP assistance were less likely than those who did not receive RWHAP assistance to have unmet needs for HIV clinical support services (aPR: 0.21; 95% CI: 0.16–0.28) and other medical services (aPR: 0.75; 95% CI: 0.59–0.96), but not subsistence services (aPR: 0.97; 95% CI: 0.74–1.27). Unmet needs for other medical services and subsistence services did not differ by RWHAP assistance among those with Medicaid, Medicare, or other healthcare coverage. Conclusions: RWHAP helped reduce some needs for uninsured persons. However, with growing socioeconomic inequities following the coronavirus disease 2019 pandemic, expanding access to needed services for all people with HIV could improve key outcomes. Abstract :